CYTOTOXICITY AND EXPRESSION STUDIES OF ANGIOGENESIS-PROMOTING GENES IN CANCER CELL LINES UNDER THE TREATMENT OF CANCER CANDIDATE DRUGS - SALAM ABBAS,; SUDHAKAR MALLA, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Human antigen R (HuR) is a member of the RNA-binding proteins which is a critical factor in mediating the proangiogenic factors resulting in angiogenesis among the tumors. During inflammation and anoxic conditions, cytokine interleukin-1 (IL-1) was found to activate the HuR which, in turn, aids in upregulation or downregulation of the hypoxia-inducible factors (HIF) 1α. The present study was designed to study the correlative effect of the cancer drug docetaxel (Taxotere) on the expression levels of HuR and HIF1α using HeLa cell lines. Materials and Methods: The drug was tested for cytotoxicity among the cancer cell lines using the lactate dehydrogenase and 3-(4)5-Dimethyl-thiazol-zyl)-2, 5, biphenyl tetrazolium bromide assay. Gene expression and correlation were found by the real-time expression of the gene members under the treatment. The same study was also confirmed using the molecular docking tools to screen for the possible potential anticancer target. Results: The drug was found to decrease the expression levels of the cytokine IL-1 along with the HuR proteins. This was also found to show a positive inhibition on the expression of HIF1α. The study was also confirmed using the molecular docking studies which are in accordance to the wet lab studies. Conclusion: The present study confirmed that the two receptors might act as potential anticancer drug targets which might aid in designing more novel drugs.